Microcontroller-driven hydrogen fuel cell car - Queirós, Hugo (2010)
This paper presents a fuel cell car with 8 minutes autonomy, capable of following a white line on a black track, using infrared sensors that detect white and black colors. A servomotor controls its direction. Guidelines to the servomotor are given by a system based on an 8051 microcontroller, according to the information it receives from the infrared sensors. The hydrogen needed by the fuel cell is produced by electrolysis, which requires an external power supply. The gas is retained on an isolated tank placed in the car. Then, it is used by the fuel cell to produce the electric energy required by the car motor.